T107. Using Functional near Infrared Spectroscopy (fNIRS) to assess brain activity of spinal cord injury patient, during robot-assisted gait. (May 2018) - Simis, Marcel; Santos, Karin; Sato, João; Fregni, Felipe; Battistella, Linamara
Abstract : Introduction: Neuroplasticity and functional brain connectivity reorganization is believed to be an important mechanism related to motor improvement of spinal cord injury (SCI) during rehabilitation program. The better understanding of this process is important for the improvement of rehabilitation therapy since it can be used as a prognostic biomarker, surrogate outcome and to guide new types of interventions, such as non-invasive brain stimulation. There is important insight from fMRI studies about cerebral changes related to SCI, however, these studies have an important limitation, since it is performed with patient lying down and in a restrict position. The functional Near Infrared Spectroscopy (fNIRS), on the other hand, allows to measure brain activity during gait in a naturalistic environment. Moreover, robot-assisted gait training allows SCI patient to perform active-assisted gait mimicking the physiological pattern. So, this study aims to demonstrate the feasibility of fNIRS to evaluate real-time activation of motor cortex in three SCI patients during robot-assisted gait. Methods: The data used in this study are from three SCI patients that are enrolled in a clinical trial (ClinicalTrials.gov Identifier: NCT02562001). Was used portable fNIRS with 32 optodes, 16 emitters and 16 detectors, positioned parallel to the coronal plane, through the Cz (10–20 EEG system). This assembly has primary focus in the primary motor cortex (M1) of both cerebral hemispheres. Before each evaluation, an automatic calibration process was performed using NIRStar software to determine an optimum amplification factor of 0.4–4.0 V for each channel (emitter-detector pair). Data preprocessing was performed with NIRSLab software. Software and hardware (NIRSport) are from NIRX Medical Technologies, Glen Head, New York. The relative changes in the concentration of oxy and deoxyhemoglobin was evaluated for each condition (standing and walking), with a duration of 30 s for each block and an interval of 5 s between each block. For the gait protocol was used robotic-assisted device Lokomat Pro (Hocoma; Zurich, Switzerland). An average containing the five trial blocks for each condition was performed to improve the signal-to-noise ratio. The differential hemoglobin index (oxyhemoglobin concentration - deoxyhemoglobin) at rest (standing) and during movement were evaluated using paired T-test. The null hypothesis was that during gait, metabolic consumption would increase in the primary motor cortex. Results: Two of the patients had an enhanced activation of M1, next to Cz, C1 and C2 (10–20 EEG system) during gait, when compared with standing position. One of the patients did not present changes in M1 brain activity. Conclusion: This study shows the viability of use fNIRS to measure brain activity of SCI patients during robot-assisted gait. Future analyses, with a larger sample, are necessary to correlate this findings with clinical outcomes.